2017
DOI: 10.1158/1078-0432.ccr-17-0528
|View full text |Cite
|
Sign up to set email alerts
|

RET Signaling in Prostate Cancer

Abstract: Purpose Large diameter perineural prostate cancer is associated with poor outcomes. GDNF, with its co-receptor GFRα1, binds RET and activates downstream pro-oncogenic signaling. Since both GDNF and GFRα1 are secreted by nerves, we examined the role of RET signaling in prostate cancer. Experimental Design Expression of RET, GDNF and/or GFRα1 was assessed. The impact of RET signaling on proliferation, invasion and soft agar colony formation, perineural invasion and growth in vivo was determined. Cellular signa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 42 publications
2
42
0
Order By: Relevance
“…A retrospective evaluation of post-docetaxel patients with CRPC in the COMET-1 and COMET-2 phase III clinical trials where cabozantinib was compared with prednisone and prednisone plus mitoxantrone suggest that a sub population may benefit from cabozantinib treatment, highlighting the importance of molecular stratification of patients for individualized treatments (2729). Recently, RET knockdown in a prostate AdCa cell line, LNCaP, was reported to restrict tumor growth, but it remains unclear if and how RET contributes to tumor progression in NEPC (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective evaluation of post-docetaxel patients with CRPC in the COMET-1 and COMET-2 phase III clinical trials where cabozantinib was compared with prednisone and prednisone plus mitoxantrone suggest that a sub population may benefit from cabozantinib treatment, highlighting the importance of molecular stratification of patients for individualized treatments (2729). Recently, RET knockdown in a prostate AdCa cell line, LNCaP, was reported to restrict tumor growth, but it remains unclear if and how RET contributes to tumor progression in NEPC (11).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, RET kinase was identified to be tyrosine phosphorylated in a CRPC patient with small cell neuroendocrine pathology (9) and as an enriched cell surface marker in NEPC (10). Further, RET knockdown restricted invasion and proliferation of prostate adenocarcinoma in vivo (11). However, it remains unclear whether RET kinase contributes to the growth of NEPC tumors and whether RET inhibition could be exploited as a therapeutic target in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…RET mutations are found to enrich in lung adenocarcinoma with NE differentiation (123,124). Knockdown of RET inhibits prostate tumor growth in vivo (125). A recent study from Justin Drake's lab has showed that RET phosphopeptides and mRNA levels are higher in NEPC than in prostate adenocarcinoma, while RET inhibitor AD80 blocks NEPC cell growth in culture and in mouse xenografts (126).…”
Section: Retmentioning
confidence: 99%
“…Elevated RET expression is detected in 50-65% of pancreatic ductal adenocarcinomas, particularly in higher grade tumors, where it promotes metastasis and perineural invasion, the spread of tumor cells along nerve fibers, which is associated with poor prognosis and tumor-related pain (Zeng et al 2008, Gil et al 2010, Amit et al 2017. In prostate adenocarcinomas, increased RET expression may increase proliferation and is also linked to perineural invasion (Dawson et al 1998, Ban et al 2017. Some level of RET expression is detected in a number of other cancers including melanoma, head and neck tumors, neuroblastoma, and lung, colon and renal cell carcinomas (Fig.…”
Section: Ret Expression In Other Tumorsmentioning
confidence: 99%